2019
DOI: 10.1111/ajt.15377
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for metastatic wild-type gastrointestinal stromal tumor in the era of molecular targeted therapies: Report of a first case

Abstract: The gastrointestinal stromal tumor (GIST) is a digestive neoplasm of mesenchymal lineage. The treatment strategy for receptor tyrosine kinase‐mutated GISTs is well defined. Wild‐type GISTs (WT‐GISTs) respond unsatisfactorily to specific kinase inhibitors. Moreover, evidence shows that repeat surgery has limited benefit. We report the case of a young female patient who was diagnosed with liver metastatic WT‐GIST, after initial radical resection and adjuvant therapy with molecular targeted drugs. Due to the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…(3) Recently, Iesari et al reported a case of wild-type metastatic GIST that was treated with a partial gastrectomy. (2) However, liver metastasis appeared under treatment with sorafenib. In the follow-up period, the patient received imatinib, sunitinib, nilotinib, and sorafenib in an attempt to control the slow tumor progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Recently, Iesari et al reported a case of wild-type metastatic GIST that was treated with a partial gastrectomy. (2) However, liver metastasis appeared under treatment with sorafenib. In the follow-up period, the patient received imatinib, sunitinib, nilotinib, and sorafenib in an attempt to control the slow tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases of patients undergoing LT for metastatic GIST have been reported. (1)(2)(3)(4) We report a patient diagnosed with massive gastricorigin GIST liver metastases unresponsive to imatinib treatment, who received a living donor LT 5 years after a subtotal gastrectomy, with no posttransplant recurrence after 41 months of follow-up.…”
Section: To the Editormentioning
confidence: 98%
“…Recently, another case report on the LT in KIT/ PDGFRA WT GIST was published, (5) but as already discussed, in the growing era of molecular-based therapies, interdisciplinary management with oncologists and transplant surgeons is necessary to improve the results of treatment and clinical practice.…”
Section: To the Editormentioning
confidence: 99%
“…A case report by Iesari et al states that liver transplantation (LT) could be an effective treatment option for liver metastatic wild‐type (WT) gastrointestinal stromal tumor (GIST) 1 …”
Section: Figurementioning
confidence: 99%
“…A case report by Iesari et al states that liver transplantation (LT) could be an effective treatment option for liver metastatic wild-type (WT) gastrointestinal stromal tumor (GIST). 1 Although we find this therapeutic approach very challenging, we believe that this statement requires some clarifications due to the following observations.…”
mentioning
confidence: 99%